Identification and recovery of rare-earth permanent magnets from waste electrical and electronic equipment. (October 2017) - Lixandru, A.; Venkatesan, P.; Jönsson, C.; Poenaru, I.; Hall, B.; Yang, Y.; Walton, A.; Güth, K.; Gauß, R.; Gutfleisch, O.
Highlights: Different WEEE were analyzed and the rare-earth permanent magnets were collected. Chemical composition evolution of Nd-Fe-B alloys over the years is illustrated. Loudspeakers from laptops and loudspeakers from flat TV contained Nd-Fe-B magnets. The amount of Nd-Fe-B could double if the loudspeakers streams are included. Abstract: Nd-Fe-B permanent magnets are a strategic material for a number of emerging technologies. They are a key component in the most energy efficient electric motors and generators, thus, they are vital for energy technologies, industrial applications and automation, and future forms of mobility. Rare earth elements (REEs) such as neodymium, dysprosium and praseodymium are also found in waste electrical and electronic equipment (WEEE) in volumes that grow with the technological evolution, and are marked as critical elements by the European Commission due to their high economic importance combined with significant supply risks. Recycling could be a good approach to compensate for the lack of rare earths (REs) on the market. However, less than 1% of REs are currently being recycled, mainly because of non-existing collection logistics, lack of information about the quantity of RE materials available for recycling and recycling-unfriendly product designs. To improve these lack of information, different waste streams of electrical and electronic equipment from an industrial recycling plant were analyzed in order to localize, identify and collect RE permanent magnets of the Nd-Fe-B type. This particular type of magnets were mainly found in hard disk drives (HDDs) from laptops and desktop computers, as well as in loudspeakers from compact products such as flat screen TVs, PC screens, and laptops. Since HDDs have been investigated thoroughly by many authors, this study focusses on other potential Nd-Fe-B resources in electronic waste. The study includes a systematic survey of the chemical composition of the Nd-Fe-B magnets found in the selected waste streams, which illustrates the evolution of the Nd-Fe-B alloys over the years. The study also provides an overview over the types of magnets integrated in different waste electric and electronic equipment.